Gingival Depigmentation in Maxillary Anterior Region Using Conventional Surgical Scraping A Case Report - Maghfiera Ihzanie; Sulistiawati; Ifadah (Sriwijaya Journal of Dentistry, 2024)
Introduction: Gingival pigmentation can result from melanin deposits in the gingival epithelial layer. This condition is caused by tobacco in cigarettes, which stimulates melanin production by melanocytes, leading to pigmentation changes in the gingiva. Gingival depigmentation is a procedure aimed at removing pigmentation from the gingiva to achieve improved aesthetic outcomes. Purpose: This case report aims to discuss the management of gingival depigmentation cases using the scalpel method in patients with smoker's melanosis. Case presentation: A 21-year-old male patient presented with complaints of brownish discoloration on his upper and lower gingiva, which he had noticed for approximately 2 years ago. Gingival depigmentation was performed using the scraping technique to remove the gingival hyperpigmentation. Conclusion: Gingival depigmentation using the scalpel technique is a recommended treatment with a simple technique and tools, easy to perform, economical, and can restore gingival aesthetics.